Central Nervous System Remyelination: Roles of Glia and Innate Immune Cells - Baaklini, Charbel S.; Rawji, Khalil S.; Duncan, Greg J.; Ho, Madelene F. S.; Plemel, Jason R. (Frontiers in Molecular Neuroscience, 2019)
In diseases such as multiple sclerosis, inflammation can injure the myelin sheath that surrounds axons, a process known as demyelination. The spontaneous regeneration of myelin, called remyelination, is associated with restoration of function and prevention of axonal degeneration. Boosting remyelination with therapeutic intervention is a promising new approach that is currently being tested in several clinical trials. The endogenous regulation of remyelination is highly dependent on the immune response. In this review, we highlight the cell biology of remyelination and its regulation by innate immune cells. For the purpose of this review we discuss the roles of microglia, and also astrocytes and oligodendrocyte progenitor cells as they are being increasingly recognized to have immune cell functions.